MatrigelBD, A Biocompatible Scaffold that Improves Gingival Mesenchymal Stem Cells Proliferation. - Brizuela, C. (2016)
MatrigelBD is a hydrogel scaffold with three-dimensional intercrossed networks of hydrophilic polymers with high water content. Human gingival tissue might represent a better source of MSCs, allowing these cells to be easily obtained in a relatively non-invasive way. The objective of this study was to evaluate the biocompatibility of MatrigelBD with GMSCs in vitro. Gingival connective tissue samples were obtained from healthy donors. Fresh tissue was minced and cultured during two weeks, after which cells at passage fourth were analyzed for their immune phenotype by flow cytometry. Differentiation into osteogenic, chondrogenic, and adipogenic lineages was induced and evaluated by culture staining. The "construct" was made of MatrigelBD with GMSC. To assess the biocompatibility, an MTT cellular proliferation assay was performed. The differentiation potential of the cells toward the osteogenic, adipogenic, and chondrogenic lineages was analyzed after 21 days of growth in MatrigelBD with induction differentiation media. The MTT analysis showed that MatrigelBD stimulated cell proliferation; the GMSCs maintained the expression of MSC markers. Importantly, the growth of GMSCs within the MatrigelBD did not interfere with the cell differentiation potential. These findings indicate that MatrigelBD is biocompatible with GMSCs, and this matrix improves cell proliferation in vitro.